2015
DOI: 10.5812/cardiovascmed.28136
|View full text |Cite
|
Sign up to set email alerts
|

Valsalva maneuver and strain-related ECG changes

Abstract: Background:During the four steps of the Valsalva maneuver (VM), opposite changes can be observed in some physiologic parameters. Manifestations of the VM in the electrocardiogram (ECG) have been studied in detail, but there have been few reports comparing VM-related biochemical and hemodynamic changes with a focus on the strain phase of the VM.Objectives:We studied strain-related ECG changes during the VM.Patients and Methods:This self-control descriptive study was conducted in 20 healthy male college students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In our study, we observed that a patient developed T‐wave inversion without any complaints or abnormal clinical findings after the maneuver was finished. Feldman et al 15 and Hosseini and Jamshir 16 has reported that a decrease in the amplitude of the T‐wave is possible during a VM, but no studies showed a development of T‐wave inversion during a VM.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we observed that a patient developed T‐wave inversion without any complaints or abnormal clinical findings after the maneuver was finished. Feldman et al 15 and Hosseini and Jamshir 16 has reported that a decrease in the amplitude of the T‐wave is possible during a VM, but no studies showed a development of T‐wave inversion during a VM.…”
Section: Discussionmentioning
confidence: 99%